2012
DOI: 10.3991/ijet.v7i2.1906
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of AutoCAD 3D Software as a Learning Support Tool

Abstract: Abstract-The aim of this study is to test the effectiveness of AutoCAD 3D software in learning of Engineering Drawing to enhance students understanding. Data were collected from a sample of students from a secondary school in Sungai Petani, Kedah. The quasi experimental design was used to find the effectiveness of the software in improving student's achievement. The result from this study shows excellent increases in student achievement after using this software. These indicate the software can help school stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
1
3
0
2
Order By: Relevance
“…The results of this study are supported by research conducted by which concluded. This study strengthens the research which states that there was an increase in student achievement after using autocad software which was applied to learning (Ziden et al, 2012). The results of the research that have been conducted show that learning automotive engineering drawings carried out online using Autocad software has been proven to improve online learning outcomes of class X (ten) students.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…The results of this study are supported by research conducted by which concluded. This study strengthens the research which states that there was an increase in student achievement after using autocad software which was applied to learning (Ziden et al, 2012). The results of the research that have been conducted show that learning automotive engineering drawings carried out online using Autocad software has been proven to improve online learning outcomes of class X (ten) students.…”
Section: Resultssupporting
confidence: 80%
“…The application of AutoCAD software as a learning support medium has effectiveness in improving student learning outcomes (Ziden et al, 2012). The increase in learning outcomes occurred after the application of the software in learning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Разработанное ПО позволяет заменить импортное программное обеспечение (Mathcad, AutoCAD и др. ), уже показавшее себя успешным при обучении и визуализации (Zakaria et al, 2012), поскольку обеспечивает в условиях промысла на борту судна возможность оперативно решать задачи для расчета и настройки параметров траловых систем, а также выявлять обоснования для их ремонта, что не позволяют сделать зарубежные ПО. Разработанное ПО удобно при эксплуатации в условиях промысла, в освоении и при использовании тралмастерами.…”
Section: обсуждение полученных результатовunclassified
“…Эффективность программного обеспечения AutoCAD 3D изучалась в Малайзии при изучении инженерного черчения для улучшения понимания учащимися (Zakaria et al, 2012). Результат этого исследования показал хороший рост успеваемости учащихся после использования этого программного обеспечения.…”
Section: Introductionunclassified